Reduced circulating sTWEAK levels are associated with metabolic syndrome in elderly individuals at high cardiovascular risk - Díaz-López, Andrés (BioMed Central, 2014)
BACKGROUND: The circulating soluble TNF-like weak inducer of apoptosis (sTWEAK) is a cytokine that modulates inflammatory and atherogenic reactions related to cardiometabolic risk. We investigated the association between sTWEAK levels and metabolic syndrome (MetS) and its components in older subjects at high cardiovascular risk. METHODS: Cross-sectional analysis of 452 non-diabetic individuals (men and women aged 55–80 years) at high cardiovascular risk. MetS was defined by AHA/NHLBI and IDF criteria. Logistic regression analyses were used to estimate odds ratios (ORs) for MetS and its components by tertiles of serum sTWEAK concentrations measured by ELISA. RESULTS: sTWEAK concentrations were lower in subjects with MetS than in those without. In gender- and age-adjusted analyses, subjects in the lowest sTWEAK tertile had higher ORs for overall MetS [1.71 (95% CI, 1.07-2.72)] and its components abdominal obesity [2.01 (1.15-3.52)], hyperglycemia [1.94 (1.20-3.11)], and hypertriglyceridemia [1.73 (1.05-2.82)] than those in the upper tertile. These associations persisted after controlling for family history of diabetes and premature coronary heart disease, lifestyle, kidney function and other MetS components. sTWEAK concentrations decreased as the number of MetS components increased. Individuals in the lowest vs the upper sTWEAK tertile had an increased risk of disclosing greater number of MetS features. Adjusted ORs for individuals with 2 vs ≤1, 3 vs ≤1, and ≥4 vs ≤ 1 MetS components were 2.60 (1.09-6.22), 2.83 (1.16-6.87) and 6.39 (2.42-16.85), respectively. CONCLUSION: In older subjects at high cardiovascular risk, reduced sTWEAK levels are associated with MetS: abdominal obesity, hypertriglyceridemia and hyperglycemia are the main contributors to this association.